NEOLOGISMS THAT ENTERED OUR LANGUAGE AND THEIR ANALYSIS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The purpose of this article is about the lexicon of the Uzbek language, i.e. the neologisms that contribute to the enrichment of the vocabulary. Today, neologisms that have entered our language and are actively used in conversation, as well as comments on their classification, are studied in detail. The article provides an analysis of the meaning of neologisms that have entered our language. These neologisms came mainly from the English language.